Support Systems, Challenges, and Coping Mechanisms of Volunteer Teachers in Elementary Schools of North District, Bayugan City Division - Llacuna, June Claire G; Cuizon, Marivic M. (RIRAI Publisher, 2025)
This study investigated the support systems, challenges, and coping mechanisms of volunteer teachers in elementary schools within the North District of Bayugan City Division, Philippines. Employing a phenomenological research design, the study explored the lived experiences of these teachers through interviews. The research aimed to understand the motivations behind their volunteerism, the difficulties they encountered, the coping strategies they utilized, and the support systems available to them. The findings revealed that volunteer teachers faced various challenges, including limited resources, lack of adequate support, and emotional strain. To navigate these challenges, they employed a range of coping mechanisms, demonstrating resilience and resourcefulness. Support systems, while often informal, played a crucial role in providing emotional and practical assistance. The study also highlighted the need for more structured support and resources to enhance the experiences and contributions of these teachers. This research contributes to a deeper understanding of volunteerism in education within resource-constrained settings and informs the development of targeted support programs for volunteer teachers in the Philippines.